(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article is based on the current aspects and necessity of personnel audit in enterprises and organizations. The essence of the audit of personnel is theoretically described, and the organizational aspects of its conduct are divided into levels, the object, directions and requirements for this process.